2011
DOI: 10.1063/1.3665211
|View full text |Cite
|
Sign up to set email alerts
|

Thermal energy transport model for macro-to-nanograin polycrystalline semiconductors

Abstract: Effective thermal conductivity of graphene-based composites Appl. Phys. Lett. 101, 121916 (2012) Assessment of phonon boundary scattering from light scattering standpoint J. Appl. Phys. 112, 063513 (2012) Visible photoluminescence in polycrystalline terbium doped aluminum nitride (Tb:AlN) ceramics with high thermal conductivity Appl. Phys. Lett. 101, 111903 (2012) Enhanced thermal conductivity of polycrystalline aluminum nitride thin films by optimizing the interface structure Understanding thermal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 34 publications
9
23
0
Order By: Relevance
“…1), a good agreement between them has been observed, demonstrating that our newly developed model for ETC is effective for nanocrystalline materials. In addition, a good agreement between our model and experimental ETC141518 for nanocrystalline silicon at 300  K (refer to Supplementary discussion 4 and Fig. S7) has also been observed, which further confirmed that our model is valid.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…1), a good agreement between them has been observed, demonstrating that our newly developed model for ETC is effective for nanocrystalline materials. In addition, a good agreement between our model and experimental ETC141518 for nanocrystalline silicon at 300  K (refer to Supplementary discussion 4 and Fig. S7) has also been observed, which further confirmed that our model is valid.…”
supporting
confidence: 85%
“…(3) better amenable to practical application, a simple theoretical ECT model for nanocrystalline materials has been proposed in this work by considering both single crystal thermal properties and the Kaptiza thermal resistance. By comparing our theoretical predictions with simulated results for the ECT of nanocrystalline diamond at 300  K as well as experimental ETC of nanocrystalline silicon141518 at 300  K , a good agreement between them has been obtained, which proves the rationality behind our ECT formula. Although the effect of both GBs and size effects can be expressed by using the grain size in this ECT formula, the mechanisms of action in these two factors on ETC are totally different151920, and further the contribution of these two factors on ETC may be different for different materials and grain sizes.…”
supporting
confidence: 60%
“…We refer to the method of Maldovan's model. [31] This model calculated the thermal conductivity for bulk polycrystalline SiC by considering intrinsic Umkplapp phonon scattering, phonon-grain boundary scattering, and thermal boundary Kapitza conductance. The present grain size d inputted in Maldovan's model was determined by counting at least 100 grains in corresponding TEM images of each sample.…”
mentioning
confidence: 99%
“…The thermal conductivity, , ranges in the literature from 0.2 up to 34 W/m/K 9 . The different material properties are a function of temperature, the crystal grains size and the film thickness 10 . To determine the sensitivity of the pellicle behavior, the thermal conductivity has been varied over the full range.…”
Section: Thermal Simulationmentioning
confidence: 99%